STUDY OF AVIAN DIVERSITY AT SELECTED SITES ALONG TARBELA DAM, INDUS RIVER, PAKISTAN - Q. Rahman; M. S. Nadeem; M. Altaf (Journal of Animal and Plant Sciences, 2023)
Tarbela Dam is a wetland in Pakistan but most of the natural landscape has been deforested and modified due to deforestation. The present study was planned to know avian diversity of Tarbela Dam, Indus River, Pakistan, which was unexplored till now. This one year research was carried out in the vicinity of the Tarbela reservoir, Indus River, Pakistan, from March 2018 to February 2019. The data were collected early in the morning (4:00 am to 7:00 am) and before sunset (5:00 pm to 6:00 pm). Data were collected from eight sub sites i.e. Kalabat, Galla, Pehure, Sobra, Labadam, Kiara, Balongi and Kabbal. During the study period, the total avian population recorded was 2697 while species were 63. The Shannon-wiener diversity index was as Kalabat (3.666), Galla (3.762), Pehure (3.662), Sobra (3.765), Labadam (3.63), Kiara (3.783), Balongi (3.585) and Kabbal (3.703). The highest Evenness index (E= 0.7993) was noted from Sobra and the lowest Evenness index (E= 0.6182) was documented from Pehure. The highest Richness/Margalef (R=10.03) was recorded from Pehure and Kiara. It may be concluded that Tarbela Dam has high avian diversity to date and should be declared a Ramsar site.
Keywords: Wetland; Richness; Margalef; Evenness; Tarbela Dam